Plant growth promotion induced by phosphate solubilizing endophytic Pseudomonas isolates - Otieno, Nicholas; Lally, Richard D.; Kiwanuka, Samuel; Lloyd, Andrew; Ryan, David; Germaine, Kieran J.; Dowling, David N. (Frontiers in Microbiology, 2015)
The use of plant growth promoting bacterial inoculants as live microbial biofertilizers provides a promising alternative to chemical fertilizers and pesticides. Inorganic phosphate solubilization is one of the major mechanisms of plant growth promotion by plant associated bacteria. This involves bacteria releasing organic acids into the soil which solubilize the phosphate complexes converting them into ortho-phosphate which is available for plant up-take and utilization. The study presented here describes the ability of endophytic bacteria to produce gluconic acid (GA), solubilize insoluble phosphate, and stimulate the growth of Pisum sativum L. plants. This study also describes the genetic systems within three of these endophyte strains thought to be responsible for their effective phosphate solubilizing abilities. The results showed that many of the endophytic strains produced GA (14–169 mM) and have moderate to high phosphate solubilization capacities (~400–1300 mg L−1). When inoculated into P. sativum L. plants grown in soil under soluble phosphate limiting conditions, the endophytes that produced medium-high levels of GA displayed beneficial plant growth promotion effects.